Warisan Mafqud dan Orang Mati Bersama Menurut Imam Mazhab dan Hukum Islam di Indonesia - Sarah; Syamsul; Abdul Jafar (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study aims to examine the legal implications for inheritance rights for parties involved in cases of mafqud (missing persons) and individuals who die together according to Islamic law and the Compilation of Islamic Law (KHI) in Indonesia. The research employs a normative legal study method with an Islamic law approach. The findings indicate that Islamic law provides specific provisions for mafqud cases, considering an individual deceased after a certain period, while in cases of individuals dying together, inheritance distribution is based on confirmation of the order of death. KHI follows a similar principle and involves religious courts in resolving inheritance disputes to ensure fairness. The discussion emphasizes the importance of consistent application of legal provisions and the crucial role of religious courts in addressing uncertainty and conflicts in inheritance distribution.